Urgensi Program Pengungkapan Sukarela (Tax Amnesty Jilid II) Berdasarkan Sudut Pandang Wajib Pajak - Adinda Suci Cahya Ningtyas; Aisyaturrahmi Aisyaturrahmi (Department of Accounting, Faculty of Economics & Business, 2022)
The purpose of this study is to examine and analyze the effect of the Voluntary Disclosure Program (VDP) on the perception of taxpayers, and is moderated by government trust. The data collection technique used in this study is convenience sampling. This study used a sample of 115 respondents from KPP Pratama Surabaya Mulyorejo. The data used are primary data obtained through questionnaires and interviews with taxpayers. The data analysis technique used validity, reliability, classical assumptions and MRA (Moderated Regression Analysis). The results of the research based on hypothesis testing, namely the Voluntary Disclosure Program (X) partially statistically has an influence on the Taxpayer Perception (Y) and moderated by the Government Trust (Z) can strengthen the influence between the regression models.